The Use Of Portfolio In Assessing Students' Writing Skills At First Grade Of SMP Amal Mulya Tawangmangu In 2014/2015 - Munawaroh, Ulumi; , Aryati Prasetyarini, M.Pd; , Nur Hidayat M.Pd (2015)
This study aims at describing the use of portfolio in assessing students' writing written by the first grade students of SMP Amal Mulya Tawangmangu. This research is a descriptive qualitative research. The subject of this research is the students of SMP Amal Mulya Tawangamangu at 7th A grade which consist of 30 students. The object of this research is the use of portfolio in assessing students' writing skill at the student of 7th grade of SMP Amal Mulya Tawangmangu, Karanganyar. The data are taken from event, informant, and document. The methods of collecting data in this research are observation, interview and analyzing document. The research findings show that there are tasks that are used to asses students writing skills like homework, group task, individual task, daily task and final task. The teacher used a procedure to make assessment with assess student's worksheet directly. The teacher used some aspect for determining assessment such as punctuation, diction, grammar and content. There are some instruments used to make assessment such as rubric score and scoring criteria. There are some problems faced by the teacher like time management, the process of scoring, and the teacher does not master the method of assessment. The conclusion is the use of portfolio assessment can improve student's ability on writing skills. There are some strengths and weakness of using portfolio assessment in writing skills. The strengths are portfolio assessment can improve students' writing skill in using words order, tenses, pronouns, vocabulary, sentence patterns, and other grammar forms. The weakness of using portfolio in assessing writing skill is that it needs more times for students to write and revise.